2020
DOI: 10.3390/toxins12060406
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal Molecular Mechanism and Toxicological Degradation of Microcystis aeruginosa by White-Rot Fungi

Abstract: Current research on the inhibition of Microcystis aeruginosa growth is primarily focused on algae-lysing bacteria, and few studies have investigated the inhibitory mechanisms by which fungi affect it at the molecular level. A comparative analysis of the effects of Phanerochaete chrysosporium on the expression of the algal cell antioxidant protease synthesis gene prx, the biological macromolecule damage and repair genes recA, grpE, and fabZ, and the photosynthesis system-related genes psaB, psbD1 and rbcL, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 37 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Studies on the efficiency of MC removal by Mucor hiemalis showed that fungal intracellularly internalized MC-LR was broken down and biotransformed into less toxic MC-LR-GSH conjugates within 24 h of exposure [ 102 ]. Zeng et al [ 103 ] found that Pseudomonas flavus not only inhibited the growth of P. aeruginosa, but its metabolites were able to inhibit the synthesis of MCs.…”
Section: Biodegradationmentioning
confidence: 99%
“…Studies on the efficiency of MC removal by Mucor hiemalis showed that fungal intracellularly internalized MC-LR was broken down and biotransformed into less toxic MC-LR-GSH conjugates within 24 h of exposure [ 102 ]. Zeng et al [ 103 ] found that Pseudomonas flavus not only inhibited the growth of P. aeruginosa, but its metabolites were able to inhibit the synthesis of MCs.…”
Section: Biodegradationmentioning
confidence: 99%
“…It has been reported that the fungus Trichaptum abietinum 1302BG can eliminate four cyanobacteria directly including M. aeruginosa FACH-918 and M. aeruginosa PCC 7806 in 48 h [106]. Some other fungi such as Trichoderma citrinoviride [6], Penicillium chrysogenum [97], Aureobasidium pullulans KKUY070 [98], Lopharia spadicea [99], Phanerochaete chrysosporium [100,101], Irpex lacteus T2b [102], Trametes versicolor F21a [107] and Bjerkandera adusta T1 [103] also show good inhibitory activities against M. aeruginosa. It has been stated that T. citrinoviride and A. pullulans have highly specific anticyanobacterial effects towards Microcystis spp.…”
Section: Anticyanobacterial Fungimentioning
confidence: 99%
“…The relative transcriptional level of some critical genes in cyanobacteria can be dramatically changed by anticyanobacterial microorganisms and substances, including genes related to the synthesis of photosystem reaction center proteins (PsaA, psaB, psbA1 and psbD1) [47,57], peptidoglycan synthesis (glmS), membrane proteins (ftsH), antioxidase (prx) [100], heat-shock proteins (grpE) [100], fatty acids (fabZ) [100], cyanotoxin microcystins (mcyA, mcyB, mcyC and mcyD) [83,97], the functions of cell division (ftsZ) [93], CO 2 fixation (rbcL) [61], and DNA repair (ftsH and recA) [2,5]. Researchers have reported that the tran-scription expressions of genes ftsZ, psbA1, and glmS are decreased by DBL that is isolated from P. noxius HN-1 [104] and bacilysin that secreted from B. amyloliquefaciens FZB42 [91].…”
Section: Effects Of Anticyanobacterial Microorganisms On Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce this, extensive studies have been consistently conducted to develop an effective method to control this cyanobacterial bloom. Consequently, the various methods for physical (e.g., clay and ultrasound), chemical (e.g., copper sulfate, naphtoquinone derivates, and hydrogen peroxide), and biological (e.g., algicidal bacteria, fungi, and protozoa) controls have been developed [7][8][9][10]. Compared to physical and chemical controls, biological control was recognized as environmentally friendly technique for controlling this cyanobacterial bloom [11].…”
Section: Introductionmentioning
confidence: 99%